Pengaruh Glimepirid terhadap Penurunan Glukosa Darah pada Mencit Diabetes-Disfungsi Ginjal - Lili Sartika; Ikha Rahardiantini (Jurnal Ilmiah Medicamento, 2022)
Diabetes mellitus (DM) is a disease or chronic metabolic disorder that can cause long-term complications such as damage to the liver, heart, eyes, and kidneys. One of the diabetes drugs is glimepiride. Glimepiride has the main mechanism of action of lowering blood glucose by stimulating insulin secretion from the granules of Langerhans cells. This study aims to determine the effect of glimepiride on reducing blood glucose in diabetic-kidney dysfunction mice. The design of this research is Post-test Only Control Group Design. This study used 105 mice which were divided into 7 groups. The dose of glimepiride was made in three variations: 1 mg/kgBW, 2 mg/kgBW and 4 mg/kgBW. The results showed no significant effect on decreasing blood glucose levels in diabetic-kidney dysfunction mice at various doses of glimepiride (p>0.05). Furthermore, further tests were carried out which showed that there was a significant effect on the duration of administration of various doses of glimepiride in reducing blood glucose levels in diabetic-kidney dysfunction mice (p<0.05). From the results of this study, it can be concluded that the pathology of the disease does not significantly affect the mechanism of action of glimepiride. Still, the length of time glimepiride is administered to diabetic-renal dysfunction mice shows a significant effect.